Microbypass stent implantation with cataract extraction and endocyclophotocoagulation versus microbypass stent with cataract extraction for glaucoma. Issue 3 (March 2017) - Ferguson, Tanner J.; Swan, Russell; Sudhagoni, Ramu; Berdahl, John P.
Abstract : Purpose : To compare the outcomes of combined microbypass stent implantation, cataract extraction, and endocyclophotocoagulation (ECP) with those of implantation of the same microbypass stent with concomitant cataract surgery in patients with open‐angle glaucoma (OAG). Setting : Private Practice, Sioux Falls, South Dakota, USA. Design : Retrospective consecutive case series. Methods : Patients from January 2015 to August 2016 were included. The study group comprised eyes that had implantation of a microbypass stent in combination with cataract extraction and ECP. To compare outcomes, a control group of eyes with similar baseline characteristics that had implantation of a stent in combination with cataract surgery was established. Data were collected preoperatively and postoperatively at 1 day, 1 week, and 1, 3, 6, and 12 months. Data included intraocular pressure (IOP) and number of glaucoma medications. Results : The mean preoperative IOP was 21.49 mm Hg ± 9.56 (SD) in the study group (51 eyes) and 20.66 ± 3.23 mm Hg in the control group (50 eyes). Twelve months postoperatively, the mean IOP reduction was 7.14 mm Hg in the study group and 4.48 mm Hg in the control group and the medication reduction was 38% (0.68) and 63% (1.06), respectively. Conclusions : Patients who had implantation of the microbypass stent in combination with cataract surgery and ECP had significantly better IOP reduction than those who did not have ECP. The combination procedure was also effective in patients with severe OAG.